(untitled) (Cardiovascular Journal, 2024)
Background: Non-ST Segment Elevated Myocardial infarction (NSTEMI) is a potentially life-threatening condition. Dyslipidaemia is a major contributor of coronary artery disease (CAD) and TG/HDL-C ratio can be an important marker for the prediction of the extent of CAD. This study was aimed to find out the relation between TG/HDL-C ratio with severity of coronary artery lesion in NSTEMI patients. Methods: A total of 200 NSTEMI patients were included and classified into two groups on the basis of TG/HDL-C ratio: Group-A (TG/HDL-C ratio ≤4, n=100) and Group-B (TG/HDL-C ratio >4, n=100). Angiographic severity was measured by Gensini score in all the patients during the same hospital stay period. Relation between TG/HDL-C ratio and angiographic severity was evaluated. Results: Mean age of the study populations was 55.13±8.49 (years) with male predominance (75%). Hypertension, diabetes mellitus, dyslipidaemia and obesity were significantly higher in Group-B (p<0.05). Gensini score in Group-B were significantly higher than Group-A (71±23 vs 30±12, p<0.001). A strong positive linear relationship was found between TG/HDL-C ratio and Gensini score (r=+0.803). Multivariate logistic regression found TG/HDL-C ratio >4 as the powerful independent predictor of Gensini score >36 (AOR=7.98, 95% CI=4.0-15.91, p<0.001). Conclusion: There is a significant positive correlation between TG/HDL-C ratio with Gensini score indicating increased severity of coronary disease in patients with NSTEMI. So early risk stratification and intensive management of NSTEMI can be done by using this cheap and easily available marker on admission. Cardiovasc j 2024; 16(2): 63-69